2019
DOI: 10.2147/prbm.s195131
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and associated factors of depression and anxiety among doctoral students: the mediating effect of mentoring relationships on the association between research self-efficacy and depression/anxiety</p>

Abstract: PurposeAlthough the mental health status of doctoral students deserves attention, few scholars have paid attention to factors related to their mental health problems. We aimed to investigate the prevalence of depression and anxiety in doctoral students and examine possible associated factors. We further aimed to assess whether mentoring relationships mediate the association between research self-efficacy and depression/anxiety.MethodsA cross-sectional study was conducted among 325 doctoral students in a medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 67 publications
3
67
1
7
Order By: Relevance
“…Self-efficacy, as one of the most important positive psychological qualities, has become a plastic internal psychological resource and can serve as a buffer against mental disorders ( 41 – 43 ). CL Liu et al demonstrated that self-efficacy was negatively correlated with the levels of both depression and anxiety among doctoral students ( 44 ). Self-efficacy training has been confirmed effective in reducing mental problems, such as anxiety and depression ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy, as one of the most important positive psychological qualities, has become a plastic internal psychological resource and can serve as a buffer against mental disorders ( 41 – 43 ). CL Liu et al demonstrated that self-efficacy was negatively correlated with the levels of both depression and anxiety among doctoral students ( 44 ). Self-efficacy training has been confirmed effective in reducing mental problems, such as anxiety and depression ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…TMMS-24: Trait Meta-Mood Scale. Burnout in Spanish PhD Students 9 Liu et al, 2019). Following this line of work, we hypothesized that burnout can be a reaction to this prolonged exposure to stress.…”
Section: Discussionmentioning
confidence: 99%
“…One way to do this could be to explore the management styles or dimensions that form the relationship. A possible starting point is the study by Liu et al (2019). These authors used a 30 item measure to assess the strength of the mentoring relationship in three dimensions: Rapport (encouragement, respect, and interpersonal warmth), apprenticeship (the degree to which the advisor teaches the advisee about professional work), and task focus (the degree to which the advisor facilitates the advisee's progress through the graduate program).…”
Section: Discussionmentioning
confidence: 99%
“…Diferentes investigaciones señalan el papel fundamental de las relaciones dentro del entorno académico a la hora de condicionar la experiencia de los doctorandos (Corcelles et al 2019), siendo especialmente relevante el papel de los directores de tesis (Evans et al 2018; González-Ocampo y Castelló 2019; Liu et al 2019). Una buena dirección influye directamente en el bienestar de un doctorando y, por tanto, puede condicionar su permanencia o no dentro del sistema académico una vez acabada la tesis, por lo que es una variable importante a considerar en un estudio como el nuestro.…”
Section: Relaciones En El Entorno Académicounclassified